THE EFFECT OF TAX AVOIDANCE, INTELLECTUAL CAPITAL, AND REAL EARNING MANAGEMENT ON FIRM VALUE - Neng Susan Nurjanah; Indah Umiyati; Icih Icih (Journal of Taxation Analysis and Review, 2024)
The study aimed to determine the effect of tax avoidance, intellectual capital, and real earning management on firm value in consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2019-2021. This type of research is quantitative research. This study uses secondary data sourced from the official website of the Indonesia Stock Exchange, namely www.idx.co.id/. The population in this study are consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2019-2021, totalling 80 companies. The sampling method used is purposive sampling method. Based on predetermined criteria, a sample of 34 companies. The data analysis method used is descriptive statistical analysis, classical assumption test, multiple linear regression test, partial test, simultaneous test and coefficient of determination with SPSS 22 analysis tool. The result of this study indicate that (1) tax avoidance has no effect on firm value, (2) intellectual capital has a negative effect on firm value, (3) real earning management has a positive effect on firm value, and (4) tax avoidance, intellectual capital and real earning management jointly affect the value of the company.